URBAN FORM, MOBILITY BEHAVIOR AND DYSFUNCTION OF TRANSPORT SUPPLY: THE CASE OF YAOUNDÉ - (:unkn) unknown (My University, 2017)
The objective of this chapter is to assess the relationship between urban form, mobility behavior, and dysfunction of transport supply in a large African city with high urban growth like Yaoundé in Cameroon. Specifically, the chapter aims at assessing the influence of urban, mobility, and socioeconomic characteristics of an origin area on the mobility choice of individuals. Using field data collected by the urban community of Yaoundé in 2010 and statistical tools such as multinomial logits, results show that urban form characteristics, such as human and establishment densities, accessibility, and origin-destination distances influence the choices of individual mobility. The urban form of major cities in Africa, due to a very high urban growth uncontrolled by the local authorities, plays a negative role on the operations of urban transport service in Africa because it promotes an artisanal supply characterized by a low capacity and reduces the efficiency and competitiveness of mass public transportation, which is cheaper. Based on results of this study, recommendations are: controlling urban sprawl, easing of accessibility to public transport, and developing an efficient and competitive mass transportation.
Keywords: African Research